Black holes in higher dimensions and gravitational collapse - Mena, Filipe C. (2012)
We summarise recent results about the gravitational collapse to black holes in higher dimensions. We construct (n+2)-dimensional collapsing space-times, which include generalised Friedmann-Lemaître-Robertson-Walker solutions, and we prove that these can be matched to static L-vacuum exterior space-times. We then investigate the global properties of the matched solutions which, besides black holes, may include the existence of naked singularities and wormholes.